2021
DOI: 10.3390/su13126934
|View full text |Cite
|
Sign up to set email alerts
|

Resident Support for Tourism Development: Application of a Simplified Resident Empowerment through Tourism Scale on Developing Destinations in Flanders

Abstract: While the potential macro-economic benefits of tourism development have been well-established, the negative social effects of uninhibited growth have received increased attention in the last decade, emphasizing the central role of communities in the search for a sustainable balance in tourism. This paper focuses on the relatively underdeveloped Scheldeland region in Flanders (Belgium), where a strategic goal is to leverage cultural and natural heritage to boost development. Via a resident questionnaire based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Furthermore, Sirakaya et al (2002) suggest that attitudes toward the tourism sector can motivate residents to support tourism development. Additionally, Neuts et al (2021) found that the perceived positive impacts of tourism have a positive relationship with support for tourism. Huong and Lee (2017) argue that social and environmental impacts from tourism play a crucial role in influencing local residents' support and participation in the tourism industry.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Sirakaya et al (2002) suggest that attitudes toward the tourism sector can motivate residents to support tourism development. Additionally, Neuts et al (2021) found that the perceived positive impacts of tourism have a positive relationship with support for tourism. Huong and Lee (2017) argue that social and environmental impacts from tourism play a crucial role in influencing local residents' support and participation in the tourism industry.…”
Section: Introductionmentioning
confidence: 99%